Ribosomal biogenesis genes play an essential and p53-independent role in zebrafish pancreas development - Provost, Elayne (Company of Biologists, 2012)
Mutations in the human Shwachman-Bodian-Diamond syndrome (SBDS) gene cause defective ribosome assembly and are associated with exocrine pancreatic insufficiency, chronic neutropenia and skeletal defects. However, the mechanism underlying these phenotypes remains unclear. Here we show that knockdown of the zebrafish sbds ortholog fully recapitulates the spectrum of developmental abnormalities observed in the human syndrome, and further implicate impaired proliferation of ptf1a-expressing pancreatic progenitor cells as the basis for the observed pancreatic phenotype. It is thought that diseases of ribosome assembly share a p53-dependent mechanism. However, loss of p53 did not rescue the developmental defects associated with loss of zebrafish sbds. To clarify the molecular mechanisms underlying the observed organogenesis defects, we performed transcriptional profiling to identify candidate downstream mediators of the sbds phenotype. Among transcripts displaying differential expression, functional group analysis revealed marked enrichment of genes related to ribosome biogenesis, rRNA processing and translational initiation. Among these, ribosomal protein L3 (rpl3) and pescadillo (pes) were selected for additional analysis. Similar to knockdown of sbds, knockdown or mutation of either rpl3 or pes resulted in impaired expansion of pancreatic progenitor cells. The pancreatic phenotypes observed in rpl3- and pes-deficient embryos were also independent of p53. Together, these data suggest novel p53-independent roles for ribosomal biogenesis genes in zebrafish pancreas development.